Nghiên cứu ảnh hưởng của AgNO3 và polyamidoamin (PAMAM) lên kích thước hạt nanocompozit Ag/PAMAM. - Khoa, Nguyễn Cửu; Dư, Cao Văn (Vietnam Journal of Chemistry, 2012)
Nanocomposites based on silver nanoparticles and nanopolymer dendritic PAMAM were synthesized. The structures were characterized by using UV-vis, NMR 1H, 13C, and TEM. Studying on the influence of silver and PAMAM on the size of nanocomposites indicated that the sizes of nanocomposites were about 10 - 50 nm and depended on the amount of AgNO3 and PAMAM based on polyester or polyamine in nanocomposites.